Societal Concerns with Biotechnology and Necessity of Regulations (Bangladesh Journal of Bioethics, 2019)
Biotechnology is the use of living systems and organisms to develop or make products, or any technological application that uses biological systems, living organisms or derivatives to make or modify products or processes for specific use. Biotechnology is a constantly evolving field of modern science. New tools and products developed by biotechnologists are useful in research, agriculture, industry and healthcare. Although it has many benefits including lowering our environmental footprint, and helping in diagnosis and treatment of diseases, it comes with its all-possible disadvantages. The four main societal concerns revolve around are ethical, safety, bioterrorism and environmental issues. This paper aims to describe those societal concerns raised by applications of biotechnology and possible regulations related to biotech innovations and policy implementation.